STANDAR SARANA PRASARANA LABORATORIUM IPA SEKOLAH MENENGAH ATAS DI WILAYAH BOGOR - Munarti Munarti; Susi Sutjihati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2018)
ABSTRACTFacilitation in education is something that can support teaching learning process at school. Laboratory is one of the important facilitation because the lab is a place where students can practice their skill through demonstration, experiment, and development of knowledge. The aim of this research is to know the availability of science laboratories in public high school and private high school in Bogor and compared it with minister regulation No. 24 year 2007. Descriptive method is used in this research with five schools chosen randomly as sample. Data collection techniques used in this research is observation and interview. The result of the finding shows that judging from five schools that has been observed which are SMA Al-Nur, SMA PGRI 4, SMAN 7, SMAN 4 and SMA PGRI 4 they are all not qualified with the minister regulation No.24 year 2007 about standard issue facilitation of high school laboratory which requires 2.4 m2 wide per student.Keyword: Senior High School, Laboratories, Facilitation